Construction method and application of gradient metallurgical composite interface between ZTA ceramic particles and alloy steel matrix

By performing gradient double-layer coating on the surface of ZTA ceramic particles and combining casting and permeation preparation technology, the problems of poor wetting and weak interface bonding between ZTA ceramic particles and alloy steel matrix are solved, which significantly improves the impact abrasive wear performance of the composite material.

CN119794333AActive Publication Date: 2025-04-11JINAN UNIVERSITY

Patent Information

Application Number
CN202510015189.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the problems of poor wetting and weak interface bonding between ZTA ceramic particles and alloy steel matrix, resulting in insufficient service reliability and life of ZTA ceramic particle-reinforced alloy steel composites under impact load and abrasive wear conditions.

Method used

By performing gradient double-layer coating on the surface of ZTA ceramic particles, the metallurgical interface is first combined with the FeZr-ZTA cladding layer and the ZTA ceramic particles, and then the metallurgical combination is achieved by using the FeZr-alloy steel cladding layer and the alloy steel matrix to achieve metallurgical combination. Then, the gradient metallurgical composite interface between ZTA ceramic particles and the alloy steel matrix is ​​prepared by casting seepage method.

Benefits of technology

The strong interface combination between ZTA ceramic particles and alloy steel matrix is ​​achieved, which significantly improves the service reliability and life of ZTA ceramic particle-reinforced alloy steel matrix composite under impact load and abrasive wear conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119794333A_ABST
    Figure CN119794333A_ABST
Patent Text Reader

Abstract

The invention discloses a construction method and application of a gradient metallurgical composite interface between ZTA ceramic particles and an alloy steel matrix. The preparation method comprises the following steps: firstly, preparing Zr-Fe alloy powder and ZTA micro powder into slurry by using ethanol, coating the surfaces of ZTA particles with the slurry, and pre-sintering to obtain ZTA particles with Zr-Fe-ZTA coating layers; the preparation method comprises the following steps: preparing a Zr-Fe-ZTA coating layer, soaking the ZTA particles with the Zr-Fe-ZTA coating layer in slurry prepared from Zr-Fe alloy powder, alloy steel powder and ethanol to realize secondary coating on the surfaces of the ZTA particles, and finally performing pressureless sintering to prepare the ZTA ceramic preform. Due to the bridge action of double-layer coating of the Zr-Fe-ZTA and the Zr-Fe-alloy steel powder, a metallurgical bonding interface is formed between ZTA ceramic and alloy steel, so that the impact abrasive wear resistance of the ZTA ceramic particle reinforced alloy steel composite material is greatly improved, and the ZTA ceramic particle reinforced alloy steel composite material can be applied to preparation and production of the ZTA ceramic particle reinforced alloy steel composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material processing, and in particular relates to a method for constructing a gradient metallurgical composite interface between ZTA ceramic particles and an alloy steel matrix and an application thereof. Background Art

[0002] With the rapid development of modern industry, the demand for the wear resistance of metal wear-resistant workpieces in harsh service conditions is increasing. Most wear-resistant parts require not only high hardness of the wear working surface, but also high toughness of the entire wear-resistant part, which is impact-resistant and not easy to break. Traditional cast iron and alloy steel are difficult to meet the requirements, and new wear-resistant metal materials are urgently needed to be developed.

[0003] Wear-resistant alloy steel is suitable for abrasive wear conditions with certain impact loads, such as mining machinery, engineering machinery, railway equipment, metallurgical equipment, etc. Generally, low-alloy wear-resistant steel has high strength, high hardness and high toughness. Its strength and hardness are higher than those of wear-resistant manganese steel, and it can replace manganese steel in non-large impact wear conditions. In addition, its plastic toughness is higher than that of wear-resistant cast iron. When used in wear conditions with certain impact loads, its service life is higher than that of wear-resistant cast iron. In recent years, in order to make it have better impact and abrasive wear resistance, researchers have tried to introduce ZTA ceramic particles as an external reinforcement phase into the alloy steel matrix, and expect to further significantly improve the impact and abrasive wear resistance of alloy steel by preparing ZTA ceramic particle reinforced alloy steel matrix composites. However, at present, alloy steel wear-resistant materials are mainly prepared by casting. In order to reduce equipment investment and quickly promote the large-scale low-cost preparation and engineering application of ZTA ceramic particle reinforced alloy steel composites, it is the best choice to use the existing alloy steel casting production line to prepare such composite materials. Due to the differences in physical and chemical properties between ZTA ceramic particles and alloy steel matrix, the key prerequisite for achieving high-quality preparation of ZTA reinforced alloy steel matrix composites by casting method is to completely solve the problems of poor wettability and weak interface bonding between ZTA ceramic particles and alloy steel matrix. Summary of the invention

[0004] To this end, the primary purpose of the present invention is to provide a method for constructing a gradient metallurgical composite interface between ZTA ceramic particles and an alloy steel matrix, that is, firstly, a mixed powder of Zr-Fe alloy powder and ZTA micropowder is mixed into a slurry with anhydrous ethanol and wrapped on the surface of ZTA particles, and after drying, sintered at 1050-1150°C. Then, the ZTA particles modified by surface sintering are immersed in a mixed slurry prepared by a mixed powder of Zr-Fe alloy powder, alloy steel powder after ball milling and anhydrous ethanol, so as to achieve secondary coating on the surface of ZTA particles. Finally, the ZTA particles with double coating layers constructed on the surface are mixed and loaded into a customized mold, and pressureless sintering is performed at 1300-1400°C to prepare a ZTA ceramic preform and cast by a casting infiltration method, thereby realizing the construction of a gradient metallurgical composite interface between the ZTA ceramic particles and the alloy steel matrix.

[0005] Another object of the present invention is to provide an application of the above-mentioned method for constructing a gradient metallurgical composite interface between ZTA ceramic particles and an alloy steel matrix.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] A method for constructing a gradient metallurgical composite interface between ZTA ceramic particles and an alloy steel matrix comprises the following steps:

[0008] (1) mixing Zr-Fe alloy powder and ZTA powder by ball milling to obtain FeZr-ZTA mixed powder; mixing Zr-Fe alloy powder and alloy steel powder by ball milling to obtain FeZr-alloy steel mixed powder;

[0009] (2) The FeZr-ZTA mixed powder of step (1) is mixed with anhydrous ethanol to obtain a slurry, and then the ZTA particles are immersed in the slurry to make the slurry adhere to the surface of the ZTA particles, the ZTA particles are taken out and dried, and the steps of immersing the dried ZTA particles in the slurry, taking out, and drying are repeated 2 to 5 times so that the surface of the ZTA particles is completely and evenly coated with the slurry, and then pre-sintered at 1050 to 1150° C. to obtain ZTA particles with a FeZr-ZTA coating layer;

[0010] (3) The FeZr-alloy steel mixed powder of step (1) and anhydrous ethanol are uniformly mixed to obtain a slurry, and the ZTA particles with a FeZr-ZTA coating layer obtained in step (2) are immersed in the slurry to uniformly coat the surface of the ZTA particles with the FeZr-alloy steel mixed powder, and the ZTA particles are taken out and dried, and finally the coated ZTA ceramic particles are placed in a mold and sintered to obtain a surface-coated activated ZTA ceramic porous preform;

[0011] (4) Fixing the ZTA ceramic porous preform obtained in step (3) in a casting cavity, casting a high-temperature alloy steel melt into the cavity, thereby constructing a gradient metallurgical composite interface between the ZTA ceramic particles and the alloy steel matrix and preparing a ZTA-reinforced alloy steel-based composite material.

[0012] Preferably, the average particle size of the Zr-Fe alloy powder and the alloy steel powder in step (1) is 200-300 mesh.

[0013] Preferably, in the Zr-Fe alloy powder of step (1), the mass percentage of Zr is 20-30%.

[0014] Preferably, the average particle size of the ZTA powder in step (1) is 5 to 8 μm.

[0015] Preferably, in the mixed powder of Zr-Fe alloy powder and ZTA micropowder in step (1), the proportion of Zr-Fe alloy powder is 30-50wt.%; in the mixed powder of Zr-Fe alloy powder and alloy steel powder, the proportion of Zr-Fe alloy powder is 10-20wt.%.

[0016] Preferably, the ball mill in step (1) is a low-speed planetary ball mill, the diameter of the grinding balls is 5 to 8 mm, the weight ratio of the grinding balls to the mixed powder is 5:1 to 8:1, the ball mill speed is 200 to 300 r / min, and the ball milling time is 300 to 420 min.

[0017] Preferably, the average particle size of the ZTA particles in step (2) is 8 to 12 meshes.

[0018] Preferably, in step (2), by weight percentage, the FeZr-ZTA mixed powder accounts for 10-15 wt.%, anhydrous ethanol accounts for 10-15 wt.%, and the remainder is ZTA particles.

[0019] Preferably, the pre-sintering time in step (2) is 60 to 120 minutes.

[0020] Preferably, in step (3), by weight percentage, the FeZr-alloy steel mixed powder accounts for 15-25 wt.%, anhydrous ethanol accounts for 20-25 wt.%, and the remainder is ZTA particles with a FeZr-ZTA coating layer.

[0021] Preferably, the temperature of the pressureless sintering in step (3) is 1300-1400°C.

[0022] Preferably, the pressureless sintering time in step (3) is 120 to 180 minutes.

[0023] Preferably, the drying in steps (2) and (3) refers to drying under vacuum conditions at 60 to 80° C. for 2 to 4 hours.

[0024] Preferably, the slurry needs to be stirred during the process of wrapping the particles in steps (2) and (3) in order to mix the raw materials evenly. The rotation speed conventionally used in the art can achieve the purpose of this step, so there is no need to limit the stirring speed. Preferably, a glass rod is used for stirring for 5 to 10 minutes.

[0025] Preferably, the ball milling mixing in step (1), the pre-sintering in step (2), and the pressureless sintering in step (3) are all carried out under an inert gas atmosphere, which may be at least one of argon, helium, and nitrogen.

[0026] Preferably, the furnace temperature of the alloy steel melt in step (4) is controlled at 1600±20°C, and the casting temperature is controlled at 1550±20°C, and slag removal and deoxidation treatment are required before casting.

[0027] Preferably, the alloy steel in step (4) is a non-manganese medium-high carbon medium-low alloy steel.

[0028] The present invention provides a ZTA reinforced alloy steel-based composite material, which is obtained by the method for constructing a gradient metallurgical composite interface between the above-mentioned ZTA ceramic particles and an alloy steel matrix.

[0029] The present invention provides application of the above-mentioned ZTA reinforced alloy steel-based composite material.

[0030] Preferably, the composite material can be widely used in fields such as metallurgy, mining, construction, machinery and electricity where impact abrasive wear conditions exist.

[0031] The present invention introduces two coating layers of ZrFe-ZTA and ZrFe-alloy steel, utilizes the high compatibility of the ZrFe-ZTA layer with the ZTA ceramic particles and the Zr-Fe-alloy steel with the alloy steel matrix, constructs a composition gradient composite metallurgical bonding interface between the ZTA ceramic particles and the alloy steel matrix, fully realizes the strong interface bonding between the ZTA ceramic particles and the alloy steel matrix, and greatly improves the service reliability and life of the ZTA ceramic particle reinforced alloy steel matrix composite material under impact load and abrasive wear working conditions.

[0032] The mechanism of the present invention is:

[0033] The present invention mainly performs a gradient double-layer coating treatment on ZTA particles. On the one hand, the metallurgical interface bonding between the ZTA ceramic particles and the gradient composite interface region is achieved by utilizing the good wettability of the FeZr-ZTA coating layer and the ZTA ceramic particles and the ability to undergo component diffusion and in-situ interface reaction. On the other hand, the metallurgical bonding between the composite interface region and the alloy steel matrix is ​​also achieved by utilizing the good intrinsic wettability of the FeZr-alloy steel coating layer and the alloy steel matrix and the ability to undergo component mutual diffusion. This further achieves the construction of a gradient composite metallurgical bonding interface between the ZTA ceramic particles and the alloy steel matrix and the preparation of high-quality composite materials by cast-infiltration method. The schematic diagram of the gradient composite metallurgical interface structure is shown in FIG. Figure 1 shown.

[0034] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0035] (1) By coating the surface of ZTA ceramic particles with a double coating layer of ZrFe-ZTA and ZrFe-alloy steel and coupling the thermal diffusion and heat-induced in-situ reaction processes during the infiltration casting process, the problems of poor wettability and weak interface bonding between ZTA ceramic particles and alloy steel were completely solved. The construction of a gradient composite metallurgical bonding interface between ZTA ceramic particles and alloy steel matrix was achieved, which significantly improved the impact abrasive wear resistance of the composite material.

[0036] (2) The raw materials used in the double-layer coating process of the present invention are low in cost and widely available. Compared with existing alloy steel products, the manufacturing cost of ZTA ceramic particle reinforced alloy steel composite materials is relatively low, which is beneficial to market promotion.

[0037] (3) The present invention has low equipment requirements and good compatibility with existing industrial equipment. The purpose of the invention can be achieved by using existing industrial production equipment, and large-scale production and industrial application are easy to achieve. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 : Schematic diagram of the gradient composite interface structure between ZTA ceramic particles and alloy steel matrix;

[0039] Figure 2 : Picture of the ZTA ceramic porous preform formed by sintering the ZTA ceramic particles coated with double layers of ZrFe-ZTA and ZrFe-alloy steel in Example 1;

[0040] Figure 3 : EDS line scanning spectrum of the gradient composite metallurgical bonding interface in the ZTA ceramic particle reinforced alloy steel matrix composite material prepared in Example 2;

[0041] Figure 4 : EDS surface scanning spectrum of the gradient composite metallurgical bonding interface in the ZTA ceramic particle reinforced alloy steel matrix composite material prepared in Example 3. DETAILED DESCRIPTION

[0042] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.

[0043] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.

[0044] The ball mill used in the embodiment is a conventional medium-low speed planetary ball mill. The alloy steel involved is a non-manganese medium-high carbon medium-low alloy steel.

[0045] Example 1

[0046] (1) First, weigh pure (purity 99.99%) Zr-Fe alloy powder (Zr content 20wt.%) with an average particle size of 200 mesh, ZTA micropowder with an average particle size of 5μm, and alloy steel powder with an average particle size of 200 mesh, and then ball-mill the Zr-Fe alloy powder (30wt.%), ZTA micropowder, and Zr-Fe powder (10wt.%) with the alloy steel powder according to the mass ratio to obtain Zr-Fe-ZTA mixed powder and Zr-Fe-alloy steel mixed powder. The ball milling process parameters used to prepare the two mixed powders are the same, specifically as follows: grinding ball diameter 5mm, ball-to-material ratio 5:1, rotation speed 200r / min, ball milling time 420min, and nitrogen as protective atmosphere.

[0047] (2) Pour the Zr-Fe-ZTA mixed powder obtained in step (1) into a container, then pour in an appropriate amount of anhydrous ethanol, and stir continuously until a thick slurry is formed, then put in the ZTA particles cleaned by ultrasonic wave (by weight percentage, the Zr-Fe-ZTA mixed powder accounts for 15%, the anhydrous ethanol accounts for 10%, and the balance is ZTA particles, and the ZTA particle size is 8 mesh), and stir continuously so that the ZTA particles are coated with the slurry, then take out and put into a vacuum drying oven at 80°C for 2h until the anhydrous ethanol is completely evaporated and removed, repeat the operation 2 to 3 times until the ZTA particles are completely coated with the slurry, finally put the dried ZTA particles into a furnace, sinter at 1150°C for 60min in a nitrogen atmosphere, cool the furnace to room temperature and take out to obtain ZTA particles coated with ZrFe-ZTA on the surface.

[0048] (3) Pour the Zr-Fe-alloy steel mixed powder obtained by mechanical ball milling in step (1) into a container, add an appropriate amount of anhydrous ethanol, and stir continuously until a thick slurry is formed, then add the ZTA particles coated once in step (2) into the slurry and stir continuously, wherein, by weight percentage, the Zr-Fe-alloy steel mixed powder accounts for 15%, the anhydrous ethanol accounts for 25%, and the balance is the ZTA particles coated once in step (2), put the obtained mixture into a corundum mold with a size of Φ40mm×60mm, and then dry it at 60°C for 5h until the anhydrous ethanol is completely evaporated, and finally put it into a sintering furnace and sinter it at 1300°C for 180min under a nitrogen protective atmosphere to obtain the desired ZTA ceramic porous preform, such as Figure 2 shown.

[0049] (4) The composite material is prepared by conventional sand casting. The prepared ZTA ceramic porous preform is fixed in the middle of the casting cavity by a thick iron wire. Alloy steel is used for the casting melt. The temperature of the molten iron out of the furnace is controlled at 1600±20°C, and the casting temperature is controlled at 1550±20°C. Deslagging and deoxidation treatment are performed before casting.

[0050] The prepared composite material was subjected to an impact abrasive wear test (MLD-10 impact abrasive wear tester). The test parameters were: impact energy 2 J / cm 2 , the abrasive is 6# quartz sand, the lower sample speed is 155r / min, the lower sample material is 45# steel, the time is 60min (15min×4 times), and the wear rate of the composite material is 0.58mm 3 ·min -1 .

[0051] Example 2

[0052] (1) First, weigh pure (purity 99.99%) Zr-Fe alloy powder (Zr content 30wt.%) with an average particle size of 300 mesh, ZTA micropowder with an average particle size of 8μm, and alloy steel powder with an average particle size of 300 mesh, and then ball-mill the Zr-Fe alloy powder (50wt.%), ZTA micropowder, and Zr-Fe powder (20wt.%) with the alloy steel powder according to the mass ratio to obtain Zr-Fe-ZTA mixed powder and Zr-Fe-alloy steel mixed powder. The ball milling process parameters used to prepare the two mixed powders are the same, specifically as follows: ball diameter 8mm, ball-to-material ratio 5:1, rotation speed 300r / min, ball milling time 300min, and nitrogen as protective atmosphere.

[0053] (2) Pour the Zr-Fe-ZTA mixed powder obtained in step (1) into a container, then pour in an appropriate amount of anhydrous ethanol, and stir continuously until a thick slurry is formed, then put in the ZTA particles cleaned by ultrasonic wave (by weight percentage, the Zr-Fe-ZTA mixed powder accounts for 10%, the anhydrous ethanol accounts for 15%, and the balance is ZTA particles, and the ZTA particle size is 12 mesh), and stir continuously so that the ZTA particles are coated with the slurry, then take out and put into a vacuum drying oven at 80°C for 2h until the anhydrous ethanol is completely evaporated and removed, repeat the operation 2 to 3 times until the ZTA particles are completely coated with the slurry, finally put the dried ZTA particles into a furnace, sinter at 1050°C for 120min in a nitrogen atmosphere, cool the furnace to room temperature and take out to obtain ZTA particles coated with ZrFe-ZTA on the surface.

[0054] (3) The Zr-Fe-alloy steel mixed powder obtained by mechanical ball milling in step (1) is poured into a container, and an appropriate amount of anhydrous ethanol is added and stirred continuously until a thick slurry is formed. The ZTA particles coated once in step (2) are added into the rubber material and stirred continuously, wherein, by weight percentage, the Zr-Fe-alloy steel mixed powder accounts for 25%, the anhydrous ethanol accounts for 20%, and the balance is the ZTA particles coated once in step (2). The obtained mixture is placed in a corundum mold with a size of Φ40 mm×60 mm, and then dried at 60°C for 5 h until the anhydrous ethanol is completely evaporated. Finally, the mixture is placed in a sintering furnace and sintered at 1400°C for 120 min under a nitrogen protective atmosphere to obtain the desired ZTA ceramic porous preform.

[0055] (4) The composite material is prepared by conventional sand casting. The prepared ZTA ceramic porous preform is fixed in the middle of the casting cavity by a thick iron wire. Alloy steel is used for the casting melt. The temperature of the molten iron out of the furnace is controlled at 1600±20°C, and the casting temperature is controlled at 1550±20°C. Deslagging and deoxidation treatment are performed before casting.

[0056] The EDS line scanning spectrum of the gradient composite metallurgical bonding interface in the prepared ZTA ceramic particle reinforced alloy steel matrix composite is shown in Figure 3 The prepared composite material was subjected to an impact abrasive wear test (MLD-10 impact abrasive wear tester), and the test parameters were: impact energy 2 J / cm 2 , the abrasive is 6# quartz sand, the lower sample speed is 155r / min, the lower sample material is 45# steel, the time is 60min (15min×4 times), and the wear rate of the composite material is 0.69mm 3 ·min -1 .

[0057] Example 3

[0058] (1) First, pure (purity 99.99%) Zr-Fe alloy powder (Zr content 27wt.%) with an average particle size of 260 mesh, ZTA micropowder with an average particle size of 7μm, and alloy steel powder with an average particle size of 300 mesh were weighed, and then Zr-Fe alloy powder (40wt.%), ZTA micropowder, and Zr-Fe powder (16wt.%) were ball-milled and mixed with alloy steel powder according to the mass ratio, so as to obtain Zr-Fe-ZTA mixed powder and Zr-Fe-alloy steel mixed powder respectively. The ball milling process parameters used to prepare the two mixed powders were the same, specifically as follows: grinding ball diameter 7mm, ball-to-material ratio 5:1, rotation speed 260r / min, ball milling time 380min, and nitrogen was used as the protective atmosphere.

[0059] (2) Pour the Zr-Fe-ZTA mixed powder obtained in step (1) into a container, then pour in an appropriate amount of anhydrous ethanol, and stir continuously until a thick slurry is formed, then put in the ZTA particles cleaned by ultrasonic wave (by weight percentage, the Zr-Fe-ZTA mixed powder accounts for 13%, the anhydrous ethanol accounts for 11%, and the balance is ZTA particles, and the ZTA particle size is 10 mesh), and stir continuously so that the ZTA particles are coated with the slurry, then take out and put into a vacuum drying oven at 80°C for 2h until the anhydrous ethanol is completely evaporated and removed, repeat the operation 2 to 3 times until the ZTA particles are completely coated with the slurry, finally put the dried ZTA particles into a furnace, sinter at 1100°C for 80min in a nitrogen atmosphere, cool the furnace to room temperature and take out to obtain ZTA particles coated with ZrFe-ZTA on the surface.

[0060] (3) The Zr-Fe-alloy steel mixed powder obtained by mechanical ball milling in step (1) is poured into a container, and an appropriate amount of anhydrous ethanol is added and stirred continuously until a thick slurry is formed. The ZTA particles coated once in step (2) are added into the rubber material and stirred continuously, wherein, by weight percentage, the Zr-Fe-alloy steel mixed powder accounts for 23%, the anhydrous ethanol accounts for 21%, and the balance is the ZTA particles coated once in step (2). The obtained mixture is placed in a corundum mold with a size of Φ40 mm×60 mm, and then dried at 60°C for 5 h until the anhydrous ethanol is completely evaporated. Finally, the mixture is placed in a sintering furnace and sintered at 1350°C for 150 min under a nitrogen protective atmosphere to obtain the desired ZTA ceramic porous preform.

[0061] (4) The composite material is prepared by conventional sand casting. The prepared ZTA ceramic porous preform is fixed in the middle of the casting cavity by a thick iron wire. Alloy steel is used for the casting melt. The temperature of the molten iron out of the furnace is controlled at 1600±20°C, and the casting temperature is controlled at 1550±20°C. Deslagging and deoxidation treatment are performed before casting.

[0062] The EDS surface scanning spectrum of the gradient composite metallurgical bonding interface in the prepared ZTA ceramic particle reinforced alloy steel matrix composite is shown in Figure 4 The prepared composite material was subjected to an impact abrasive wear test (MLD-10 impact abrasive wear tester), and the test parameters were: impact energy 2 J / cm 2 , the abrasive is 6# quartz sand, the lower sample speed is 155r / min, the lower sample material is 45# steel, the time is 60min (15min×4 times), and the wear rate of the composite material is 0.61mm 3 ·min -1 .

[0063] Comparative Example 1

[0064] (1) Wash the 8-mesh ZTA particles with alcohol (to remove the oil and impurities on the surface of the ZTA particles) and place them in a vacuum drying oven at 70°C for drying. Weigh an appropriate amount of ZTA particles with an electronic scale, and fully stir and evenly mix the ZTA particles and water glass binder (about 10% of the mass of ZTA). Subsequently, press the mixed ZTA particles into a mold, apply appropriate pressure to press the ceramic preform into shape, and then place the preform together with the mold into a drying oven (70°C, 5h). After drying, take out the molded ceramic preform. The mold size used is Φ40mm×60mm, and a layer of graphite paper can be placed inside the mold to facilitate demolding.

[0065] (2) The composite material is prepared by conventional sand casting. The ZTA ceramic preform is fixed inside the sand mold cavity with a thick iron wire. Circuit smelting is adopted. Alloy steel is used as the casting melt. The temperature of the molten iron out of the furnace is controlled at 1600±20℃, and the casting temperature is controlled at 1550±20℃. Deslagging and deoxidation treatment are performed before casting.

[0066] In the ZTA ceramic particle reinforced alloy steel composite material prepared in Comparative Example 1, the wettability of the ZTA particles and the alloy steel liquid is quite different, and the ZTA particles do not react with the molten iron during the casting process, and there is no dissolution and precipitation phenomenon. Obvious physical gaps can be observed at some interfaces under a high-power microscope, so the interface between the ZTA particles and the alloy steel matrix is ​​a mechanical bond.

[0067] The prepared composite material was subjected to an impact abrasive wear test (MLD-10 impact abrasive wear tester). The test parameters were: impact energy 2 J / cm 2 , the abrasive is 6# quartz sand, the sample speed is 155r / min, the sample material is 45# steel, the time is 60min (15min×4 times), and the wear rate of the composite material is 0.91mm 3 ·min -1 .

[0068] The impact abrasive wear rates of the composite materials prepared in Examples 1-3 and Comparative Example 1 are shown in the following table.

[0069] Table 1

[0070]

[0071] As can be seen from Table 1, the impact abrasive wear resistance of the composite materials obtained in Examples 1-3 has certain differences, but are significantly higher than the impact abrasive wear resistance of the composite material prepared in Comparative Example 1.

[0072] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for constructing a gradient metallurgical composite interface between ZTA ceramic particles and an alloy steel matrix, characterized in that: The following steps are involved: (1) mixing Zr-Fe alloy powder and ZTA powder by ball milling to obtain FeZr-ZTA mixed powder; mixing Zr-Fe alloy powder and alloy steel powder by ball milling to obtain FeZr-alloy steel mixed powder; (2) The FeZr-ZTA mixed powder of step (1) is mixed with anhydrous ethanol to obtain a slurry, the ZTA particles are immersed in the slurry, the slurry is adhered to the surface of the ZTA particles, the ZTA particles are taken out and dried, and the steps of immersing the dried ZTA particles in the slurry, taking out, and drying are repeated 2 to 5 times so that the surface of the ZTA particles is completely and evenly coated with the slurry, and then pre-sintered to obtain ZTA particles with a FeZr-ZTA coating layer; (3) The FeZr-alloy steel mixed powder of step (1) and anhydrous ethanol are uniformly mixed to obtain a slurry, and the ZTA particles with a FeZr-ZTA coating layer obtained in step (2) are immersed in the slurry to uniformly coat the surface of the ZTA particles with the FeZr-ZTA coating layer with the FeZr-alloy steel mixed powder, and then the coated ZTA ceramic particles are placed in a mold and sintered to obtain a surface-coated activated ZTA ceramic porous preform; (4) Fixing the ZTA ceramic porous preform obtained in step (3) in a casting cavity, casting a high-temperature alloy steel melt into the cavity, realizing the construction of a gradient metallurgical composite interface between the ZTA ceramic particles and the alloy steel matrix, and obtaining a ZTA reinforced alloy steel matrix composite material.

2. The construction method according to claim 1, characterized in that: In the Zr-Fe alloy powder of step (1), the mass percentage of Zr is 20-30%; In the mixed powder of Zr-Fe alloy powder and ZTA micropowder in step (1), the proportion of Zr-Fe alloy powder is 30-50wt.%; in the mixed powder of Zr-Fe alloy powder and alloy steel powder, the proportion of Zr-Fe alloy powder is 10-20wt.%.

3. The construction method according to claim 1 or 2, characterized in that: In step (2), by weight percentage, the FeZr-ZTA mixed powder accounts for 10-15 wt.%, anhydrous ethanol accounts for 10-15 wt.%, and the balance is ZTA particles; In step (3), by weight percentage, the FeZr-alloy steel mixed powder accounts for 15-25wt.%, anhydrous ethanol accounts for 20-25wt.%, and the remainder is ZTA particles with a FeZr-ZTA coating layer.

4. The construction method according to claim 1 or 2, characterized in that: The average particle size of the Zr-Fe alloy powder and the alloy steel powder in step (1) is 200-300 meshes; The average particle size of the ZTA powder in step (1) is 5 to 8 μm; The average particle size of the ZTA particles in step (2) is 8 to 12 meshes.

5. The construction method according to claim 1 or 2, characterized in that: The pre-sintering temperature in step (2) is 1050-1150° C. and the time is 60-120 min. The pressureless sintering temperature in step (3) is 1300-1400° C. and the sintering time is 120-180 min.

6. The construction method according to claim 1 or 2, characterized in that: In step (4), the furnace temperature of the alloy steel melt is controlled at 1600±20° C., and the casting temperature is controlled at 1550±20° C.; The alloy steel in step (4) is non-manganese medium-high carbon medium-low alloy steel.

7. The construction method according to claim 1 or 2, characterized in that: The ball mill in step (1) is a low-speed planetary ball mill, the ball diameter of the grinding balls is 5 to 8 mm, the weight ratio of the grinding balls to the mixed powder is 5:1 to 8:1, the ball mill speed is 200 to 300 r / min, and the ball milling time is 300 to 420 min.

8. The construction method according to claim 1 or 2, characterized in that: The ball milling mixing in step (1), the pre-sintering in step (2), and the pressureless sintering in step (3) are all carried out under an inert gas atmosphere, and the inert gas is at least one of argon, helium and nitrogen.

9. A ZTA reinforced alloy steel matrix composite material, characterized in that: The invention is obtained by the method for constructing a gradient metallurgical composite interface between ZTA ceramic particles and an alloy steel matrix as described in any one of claims 1 to 7.

10. Application of the ZTA reinforced alloy steel-based composite material according to claim 9 in the fields of metallurgy, mining, construction, machinery and electric power.

Citation Information

Patent Citations

  • Preparation process of composite preform

    CN101899586A

  • Method for preparing ZTA particle-reinforced metallic-matrix abrasion-resistant composite material through powder metallurgy

    CN106191496A

  • Metal-ceramic gradient composite armor and manufacturing method thereof

    CN110895122A

  • A Ceramic Reinforced Metal Composite For Hermetic Bodies For Implantable Devices

    US20230085958A1

Cited By

  • Wear-resistant alloy steel, plate hammer structure and crushing cavity structure for crusher

    CN121951376A